Aromatic Herbs as a Source of Bioactive Compounds: An Overview of Their Antioxidant Capacity, Antimicrobial Activity, and Major Applications - Leontina Grigore-Gurgu; Loredana Dumitrașcu; Iuliana Aprodu (Molecules)
Many aromatic herbs are conventionally used for flavoring various foods, but receive wide attention because of the variety of health-related properties. The aromatic herbs can be used either fresh or as dried powders and in the form of extracts, essential oils, or purified metabolites. In this review, the main functional properties, in terms of antioxidant and antimicrobial properties, and the applications of some of the commonly used aromatic herbs from the Lamiaceae family, are discussed. Herbs like oregano, rosemary, sage, thyme, summer savory, marjoram, and basil possess high levels of bioactive phytochemicals. They are particularly rich in phenolic acids, flavones, phenolic diterpenes, and flavanones, with various beneficial effects. The phytochemical profile of aromatic plants is highly influenced by genetic factors, environmental conditions, and their interaction. In cases of the extracts and essential oils, the extraction method has a strong effect on the final composition of the herb products. Most of the applications of these aromatic herbs are related to their antioxidant, antimicrobial, and flavoring properties. In particular, aromatic herb extracts and essential oils have multiple applications in fields like food, feed, pharmaceutical, cosmetics, biopesticides, and textile industries.